Historical Basis of Consolidation and Development of the Ukrainian Nation: Experience, Problems, Suggestions - Парахіна М. (Видавничо-поліграфічний центр "Київський університет", 2014)
Analyzes the principal groundworks of domestic and foreign researchers in the field of investigation and the disclosure of the basic theories of nation and nationalism. It highlights the main and most characteristic of scientific and theoretical elaborations concerning the origin and development of nations, and in particular of the Ukrainian nation.

Аналізуються ключові напрацювання вітчизняних та зарубіжних дослідників у галузі дослідження та розкриття основних теорій нації та націоналізму. Висвітлено магістральні й найхарактерніші науково-теоретичні розробки щодо походження та розвитку націй, і української нації зокрема.
Історичні засади консолідації та розвитку української нації: досвід, проблеми, пропозиції
Keywords: nation; nationalism; the Ukrainian national idea; people; нація; націоналізм; українська національна ідея; народ